2013
DOI: 10.1016/j.immuni.2013.08.038
|View full text |Cite|
|
Sign up to set email alerts
|

Germinal Center Centroblasts Transition to a Centrocyte Phenotype According to a Timed Program and Depend on the Dark Zone for Effective Selection

Abstract: SummaryGerminal center (GC) B cells cycle between the dark zone (DZ) and light zone (LZ) during antibody affinity maturation. Whether this movement is necessary for GC function has not been tested. Here we show that CXCR4-deficient GC B cells, which are restricted to the LZ, are gradually outcompeted by WT cells indicating an essential role for DZ access. Remarkably, the transition between DZ centroblast and LZ centrocyte phenotypes occurred independently of positioning. However, CXCR4-deficient cells carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
248
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(288 citation statements)
references
References 33 publications
(70 reference statements)
37
248
3
Order By: Relevance
“…Because we observed increased surface TGFβR2 on KO B cells, we assessed surface levels of other receptors critical for B-cell function in GCs (29). GC B cells from Pp and mesenteric LNs (mLNs) of KO mice had higher surface levels of CXCR4, compared with equivalent B cells from WT controls, whereas B220 levels were not affected in the KO (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because we observed increased surface TGFβR2 on KO B cells, we assessed surface levels of other receptors critical for B-cell function in GCs (29). GC B cells from Pp and mesenteric LNs (mLNs) of KO mice had higher surface levels of CXCR4, compared with equivalent B cells from WT controls, whereas B220 levels were not affected in the KO (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Spleen, mesenteric lymph node, and Peyer's patch cells were isolated and labeled for FACS analysis as described previously (29). Antibodies used for GC B-cell identification, Ig isotype detection, mixed bone chimera analysis, and labeling of TGFβR2, CXCR4, and CXCR5 are specified in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1C). Recent reports have also shown low levels of APE1 transcripts in the GC (34,35), especially in the rapidly proliferating centroblasts of the dark zone, relative to centrocytes in the light zone where selection occurs. Cultured spleen B cells express roughly equivalent amounts of APE1 and APE2 mRNA (Fig.…”
Section: Ape1mentioning
confidence: 95%
“…These results suggest that accessory molecules regulating individual cross-talks between Tfh and GC B cells may significantly impinge on qualitative and quantitative nature of affinity maturation. Furthermore, experimental studies of chemotaxis-based GC dynamics and zoning have revealed that genetic ablation of CXCR4 from the majority of GC B cells abrogates the GC LZ-DZ segregation but leaves GC maintenance and cyclic reaction relatively normal (22). FOXO1-mediated transcription regulation intrinsically dictates the DZ state (23,24).…”
mentioning
confidence: 99%